(untitled) (Applied Biological Research, 2011)
The investigation was undertaken to assess the status of haemorrhagic septicaemia (HS) in cattle and buffalo in Uttar Pradesh (India). Conventional methods were used for the diagnosis of HS and counter immunoelectrophoresis (CIE) method for epidemiological and capsular typing of Pasteurella multocida, the organism involved in HS. A total of 25 isolates were obtained and identified as P. multocida serotype B. The isolates were recognized into 12 biotypes on the basis of sugar fermentation tests thus indicating the involvement of multiple strains of P. multocida serotype B in the study area. Bipolar characteristic was exhibited in 25 samples (blood and impression smears of vital organs). The presence of antibodies against P. multocida B:2 in 10 (22.2%) serum samples by CIE showed the prevalence of P. multocida B:2 infection in the area. The results indicated that conventional methods (bipolar staining and CIE) are useful for rapid epidemiological investigations of HS.